2015
DOI: 10.1056/nejmc1500421
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Babies after Intrauterine Transfer of Mosaic Aneuploid Blastocysts

Abstract: 2089 correspondence reflects improvements in patient care rather than case selection.In response to de Miguel-Yanes et al.: we did not evaluate the subgroup with diabetes in our initial analysis. However, in contrast with de MiguelYanes et al., after stratifying our sample according to the presence of diabetes we observed higher mortality for the subgroup of patients with diabetes, and this difference persisted over time.We agree with Hussain and Al-Omran that surgical volume is an important predictor of outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
371
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 473 publications
(415 citation statements)
references
References 5 publications
(5 reference statements)
20
371
1
3
Order By: Relevance
“…Overall, 8/22 biopsies (36.6 %) revealed either mosaicism or inconclusive results. Also supporting above described mouse study, two independent groups reported surprisingly high live birth rates of healthy, genetically normal infants after transfer of embryos after PGS 2.0 reported to be aneuploid (mosaic) [15,16]. These results are indicative of significant false-positive rates following PGS 2.0 and raise serious concerns about the potential discarding of perfectly normal embryos in large quantities in current PGS 2.0 utilization.…”
Section: The Biology Of Mosaicismsupporting
confidence: 63%
“…Overall, 8/22 biopsies (36.6 %) revealed either mosaicism or inconclusive results. Also supporting above described mouse study, two independent groups reported surprisingly high live birth rates of healthy, genetically normal infants after transfer of embryos after PGS 2.0 reported to be aneuploid (mosaic) [15,16]. These results are indicative of significant false-positive rates following PGS 2.0 and raise serious concerns about the potential discarding of perfectly normal embryos in large quantities in current PGS 2.0 utilization.…”
Section: The Biology Of Mosaicismsupporting
confidence: 63%
“…A recent case series by Greco, Minasi, and Fiorentino detailed the intentional transfer of mosaic embryos, determined via aCGH, to 18 pre-counseled women. Each woman had one mosaic blastocyst available [34]. Eight pregnancies (positive hCG testing) with six singleton full-term infants resulted in this group and all babies were confirmed to have a normal karyotype.…”
Section: Technological Failurementioning
confidence: 99%
“…In the group of women older than 40 years studies with PGS on trophoblast cells have shown that a large number of embryos produced are chromosomally abnormal, thus explaining at least in part why there is such high BEmbryo Wastage^in this age group [16,34]. However, it remains to be seen whether this technique will ultimately lead to a significant improvement in live birth rate since it is still error-prone with the risk of discarding embryos wrongly diagnosed as aneuploidy because of mosaicism [21][22][23]. Other barriers such as the cost, including the possible need to cryopreserve embryos and defer transfer, and invasiveness of the biopsy and any potential long term effects also need to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Recent improvements in pre-implantation genetic screening (PGS) techniques for identifying normal euploid embryos have been associated with higher pregnancy and delivery rates when analyzed per transfer [15][16][17]; however, several barriers to its widespread use still exist, including cost and particularly the lack of unequivocal evidence that its use improves pregnancy and live birth rates, particularly for patients with few embryos available for testing, due to the presence of high rates of mosaicism in the trophoblast cells [18][19][20][21][22][23]. Other studies have reported on the use of proteomics and metabolomics to identify factors in embryo culture media that may be predictive of embryo competence or assessing gene expression in cumulus cells; however, even these methods are still inefficient and not ready yet for clinical application [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%